(untitled) (Daffodil International University Journal of Science and Technology, 2010)
Washing is one of the most important finishing treatments applied on apparels that have great usage to create special outlooks and improving the fashion. Technologically denim washing is the most important fashion element for clothing industry. Usually the term ‘washing’ is most significantly applied in case of sewn apparels so it is very essential to observe the effects that have been made by particular washing on the fabrics to hold the qualities of sewn apparels. The aim of this paper is to determine the effects of sand blasting with industrial enzyme silicon wash on denim apparel characteristics. For this investigation currently fashionable regular denim (100% cotton with twill 3/1 weave construction) trouser was chosen. The selected denim trouser has been processed by enzyme and silicon washes after sand blasting. In order to evaluate the washing effects on denim trouser, changes of fabric handle, fabric specification (ends/inch, picks/inch, surface density, warp & weft yarn linear density), fabric strength, seam strength & fabric stiffness has been determined after sandblasting with enzyme silicon wash. Keywords: Denim apparel, sand blasting, back staining, pumice stones, enzyme wash. DOI: 10.3329/diujst.v5i1.4377 Daffodil International University Journal of Science and Technology Vol.5(1) 2010 pp.6-9